On leaving criminal organizations - Bovenkerk, Frank (2011)
"Terrorist organizations, groups, cells or just ‘bunches of guys’ are systematically compared with other types of criminal or deviant organizations: organized crime such as the mafia, street gangs and religious sects. Of course there are many differences between them, especially where motivation is concerned, but they share the common factor that it is almost impossible or very difficult for individual members to step out. However, de-radicalization may follow analogous paths: aging out, accepting exit programs in prison or disengaging ideologically. The article discusses the obstacles that a government strategy that encourages desistance from terrorism by stepping out may encounter. It may be sufficient and more realistic to discourage radicals from using violence than to try to de-radicalize them by using counternarrative techniques." [author's abstract]